Identification of the Key Causes and Measures to Prevent Building Collapses in Nigeria - Nwosu, Chiemezie Chisom; Zima, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Buildings collapse in the Nigerian major urban cities continues to engender an excessive number of fatalities, injuries and property damage. The collapse of building infrastructure, though prominent in developing economies, is a worldwide issue. Building developments collapse at the construction stages and in some cases after commissioning. Examples abound in recent times in Abuja and Lagos. The major problem is the unquantifiable resources wasted when building construction development collapses.
Keywords: building collapse; construction project management; project strategy; preventing building collapses; katastrofa budowlana; projekt budowlany; infrastruktura budowlana; zapobieganie zawaleniom budynków; Nigeria